Masa Depan Aliran Bebas Madzhab: Kritik Terhadap Kejumudan Aliran La Madhhabiyah - Muhammad Asrori (Proceedings of Annual Conference for Muslim Scholars, 2017)
Islam as a religion that the plenary should be shalih li kulli zamÃ¢n wamakÃ¢n. It means that Islam can be Adaptive and developing appropriate structure of era and place. However, as a religion, Islam is not a mere set of values, but also hassome clear legal rules for the believer. And that in accordance with the rules of guidance locus and tempus, Islamic law need to evolve. So intellectuals, Muslim scholars also make the methodology of Islamic law jurisprudence, so that Islamic law is not stagnant, old-fashioned and stiff. So, Islam appeared several genre of law in Islam called Madhhab. Madhhab or madzhab is a codification of Islamic law which is generated by the priest mujtahid. However this is not necessarily approved by the Muslims entirely. Some of the Muslim, reject the madzhab because they think it is just bid'ah, and the efforts "rival" madzhab of islam actually, Rasulullah's madzhab. An invitation to return to the Al-Qur'an and Al-Hadith finnally called. This day the development is also massive through social media. Call to purify the religion of Islam, with direct reference to the Quran and Al Hadith. Unfortunately that development is not supported by conceptual development. Actually, solicitation and this genre is weak ontological, epistemological even in the realm of Axiological. Since seeing the spread of Islam and the condition of Muslims today, so is not possible to produce the law of the Quran and Al Hadith directly.Keywords: Madzhab, epistemological, Quran, Al Hadith